Gender, Justice, and the Wars in Iraq: A Feminist Reformulation of Just War Theory - Sjoberg, Laura (Lexington Books, 2006)
Gender, Justice, and the Wars in Iraq offers a feminist critique and reconstruction of just war theory. It points out gender biases in the just war tradition and suggests alternative jus ad bellum and jus in bello standards that emphasize women, political marginality, and empathy. Laura Sjoberg applies this feminist just war theory to analyze the wars in Iraq since the end of the Cold War—the First Gulf War, the war of sanctions, and the Second Gulf War. By examining international political discourse from and about Iraq, it shows where war generally and just war specifically are gendered. Through the stories of key just war characters like Jessica Lynch, this book reveals where women are omitted and subordinated in global politics. Sjoberg suggests that dialogue and empathy replace righteousness in just war thinking for the good of human safety everywhere and concludes with alternative visions of Gulf War policies, inspired by feminist just war theory.